Determinación de la presencia de nematodos fitoparásitos en plantaciones de tomate de árbol (cyphomandra betacea) en las provincias de Imbabura y Pichincha - Moreta Quilca, Gustavo (2011)
The tree tomato is an of importance cultivation economic in Ecuador and it is affected severely for problems fitosanitarios as nemátodos and pathogenic. This work conducted it to him with the technical direction of the University Técnica of Babahoyo, extension The angel and the analyses nematológicos made himself in the Experiment station of the INIAP'S Coastal Sur Dr. Enrique Ampuero Pareja. The work's objective was to determine damages and the levels nemátodos fitoparásitos poblacionales in plantations of Imbabura's provinces and Pichincha, situated to 1200 altitude to 3000 m.s.n.m. In the provinces 20 plantations with a 100- plants total that one extracted roots in one in sampled hole of 8 dm3 ( 20 cm x 20 cm x 20 cm ) and a ground sign in order to the respective analysis themselves of Imbabura nematológico. Equally one proceeded with the province of the Pichincha. The signs were taken at random, preferably to plants thereof height. Agallamiento’s index utilizing Bridge's graphic scale was evaluated in the roots. The roost’s nemátodos extracted himself for Licuado's method - once was sieved and of the ground with Incubation’s method.